Macrofungal diversity and ecology in two Mediterranean forest ecosystems. (3rd May 2016) - Angelini, P.; Compagno, R.; Arcangeli, A.; Bistocchi, G.; Gargano, M. L.; Venanzoni, R.; Venturella, G.
Abstract : The macrofungal species richness and community assemblages in Italian native woodlands of oaks and Carpinus betulus and non-native woodlands of Pinus spp., Cupressus sempervirens and Eucalyptus camaldulensis were examined through the collection of basidiomata and ascomata over 1 year. The sampling in Collestrada (Umbria) and Pizzo Manolfo (Sicily) forests revealed 216 species of macrofungi. The results indicate differences in macromycete richness and diversity patterns between the two sites. The dominant tree species of the two sites were different; thus, the Collestrada forests had higher mycorrhizal species richness, while the Pizzo Manolfo forest had a higher relative number of saprotroph macrofungi. The macrofungal community of Quercus frainetto woodland from Collestrada forest was richer and more diverse than the other site's woodland types. This study highlighted that both Collestrada and Pizzo Manolfo forests provide a habitat for diverse macrofungal species, not in the least ectomycorrhizal species.